DARI DAPUR KE DUNIA MAYA: PEMASARAN PRODUK TATA BOGA MELALUI MEDIA SOSIAL DI MEDAN - Girsang, Deddy Ray; Saragih, Vina Gabriella; Ramadhaningtyas, Chitra Annisa; Damanik, M. A. Jaya (Jurnal Manajemen dan Bisnis, 2025)
This study discusses the role of social media as a dominant force in marketing strategies, particularly in the culinary industry in Indonesia, with a focus on the city of Medan. In recent years, the rapid growth of social media users has created significant opportunities for businesses to leverage these platforms in reaching a broader consumer base. This research refers to previous studies that show social media not only functions as a promotional tool but also as a means to build more interactive relationships between businesses and consumers. By understanding this dynamic, businesses in the culinary sector can formulate more effective marketing strategies that are responsive to consumer needs, thus enhancing their competitiveness in an increasingly competitive market. This study is expected to provide valuable insights for entrepreneurs on how to optimally utilize social media to achieve their marketing objectives.